Pegylated interferon alfa-2a is effective and decreases LDH levels in patients with essential thrombocythemia and polycythemia vera - Ekinci, O. (Pergamon-Elsevier Science Ltd, 2019)
[Abstract Not Available]
10th Eurasian Hematology Oncology Congress -- OCT 08-11, 2019 -- Istanbul, TURKEY